Village Government Roles in Managing Flood Disasters in Kebonsari: Peran Pemerintah Desa dalam Mengelola Bencana Banjir di Kebonsari - Kozin; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2025)
General Background: Flood disasters remain one of the most frequent and destructive natural hazards in Indonesia, particularly affecting low-lying regions with inadequate drainage systems. Specific Background: Kebonsari Village in Candi District is a recurrent flood-prone area where seasonal inundation continues to disrupt community welfare and infrastructure. Knowledge Gap: Previous studies have focused mainly on regional or national disaster responses, leaving limited understanding of the village government's role in localized flood management. Aims: This study aims to analyze the role of the Kebonsari Village Government in managing flood disasters through the theoretical framework of Ryass Rasyid, which includes the roles of regulator, dynamicator, facilitator, and catalyst. Results: The findings reveal that the regulatory and facilitative roles have been executed fairly well, though financial limitations hinder full implementation. The catalytic role through multi-stakeholder coordination with BPBD and the community has shown significant progress. Novelty: This study provides a grounded analysis of village-level governance in disaster management within a decentralized context. Implications: Strengthening financial allocation, community participation, and inter-institutional coordination can improve sustainable local disaster resilience. Highlights: Village governance shapes effective local disaster response. Coordination and community involvement remain critical gaps. Strengthened local capacity builds long-term resilience. Keywords: Village Government, Flood Management, Public Policy, Disaster Resilience, Governance